Determination of the Detection Limit of the Detection of GMO in Food Using the Isothermal Solid-Phase Recombinase Polymerase Amplification on Microfluidic DVDs (Asian Journal of Plant Biology, 2021)
A major drawback of the current literature on bioassay development is that these tests are not made using statistically robust methods for establishing the limit of detection. As an alternative, researchers often make use of simple detection-limit methods that are only roughly indicative of the actual detection limit. We can only assume that this is due to a practical need for simplified processes, in addition to the notion that the limit of detection theory has already been lowered to practice for bioassays. A DNA sensor based on light intensity of the scanning laser on a DVD drive with microfluidic layer etched onto the polycarbonate surface of an ordinary DVD has been previously developed for fast screening of genetically modified organisms (GMOs). The resultant calibration curve showed a sigmoidal calibration curve but was not modelled according to any of the sigmoidal models available. The objective of this study is the remodel the data using the standard 4-PL model and to determine the Limits of Detection (LOD) based on the standard method. The LOD value obtained through the 4PL modelling exercise based on a pooled standard deviation method yielded an LOD value of 62 mg/g (95% confidence interval of 17 to 158), which was quite similar to the classical three standard deviation of the blank method but was lower than the rough estimation employed in the original publication.
Keywords: Limit of the Detection; GMO; Isothermal Solid-Phase Recombinase Polymerase Amplification; Microfluidic DVDs